Biodiesel derived from waste cooking oil in blends with ultra-low sulphur diesel and its spray macroscopic properties under split injection strategy. Issue 3 (16th March 2023) - Mena-Cervantes, Violeta Y.; Martínez-Martínez, Simón; de la Garza, Oscar A.; Hernández-Altamirano, Raúl; García-Yera, Miguel; Altamirano-Muratalla, Miguel F.
Abstract: There is a significant interest to evaluate alternative injection strategies in order to improve the performance of biofuels and its blends in internal combustion engines as a way to decarbonize the transport sector, particularly in high potence demand niche. Biodiesel is the renewable analogue for petroleum diesel but the performance assessment of its blends from related to their spray macroscopical properties is scarce in the literature. This article evaluates the effect of Waste Cooking Oil Biodiesel (WCO) produced at semi-industrial scale in blends (B05, B10, B20) with commercial Ultra Low Sulphur Diesel (ULSD) on the fuel spray macroscopic properties such as penetration, angle, and area when a split injection strategy is used in a constant volume chamber under non-reactive and evaporative conditions using an injection and back pressure of 120 MPa and 5 MPa, respectively. These results were analysed in conjunction with relevant physicochemical properties of the fuels to identify the optimum diesel-WCO biodiesel blend, that could be implemented in a conventional diesel engine. It was observed that the increase of density and viscosity directly influences spray tip penetration, whereas surface tension affects spray angle. The values of spray penetration and spray area of all fuels during the second injection were higher than those of the first injection. Accordingly, the first injection event provokes an improvement mixing process of the second injection event in all cases. The values of spray penetration and area corresponding to B10 and B20 were higher than those of B5 and ULSD in both injection events at all times. Therefore, the split injection could be an effective strategy to improve the mixing process of biodiesel blends as well as the efficiency and emission performance in conventional diesel engines.